Efektifitas penerapan diabetes self management education(DSME)terhadap motivasi penderita dalam mencegah kekambuhan dan komplikasi penyakit diabetes melitus - siti damawiyah; Yurike Septianingrum (Universitas Nahdlatul Ulama Surabaya, 2020)
Diabetes mellitus is a chronic disease that is still a major problem in health both in the world and in Indonesia. Diabetes mellitus is a group of metabolic diseases with characteristics of hyperglycemia that occur due to abnormal insulin secretion, insulin action or both. The purpose of this study was to determine the effect of the application of Diabetes Self Management Education (DSME) on patient's motivation in preventing recurrence and complications of diabetes mellitus inRW01,WonokromoVillage,Surabaya.                This research is a type of quantitative research using the Quasy Experimental design, Pre Test-Post Test Design Control Group. The population in this study were 24 people with diabetes mellitus. The sample in this study were some DM patients who met the criteria of 10 intervention groups and 10 control groups. The independent variable in this study was the application of DSME, the dependent variable in this study was the motivation of patients to prevent recurrence and complications of DM disease. Data analysis using the Mann Withney test.               The results showed that the motivation of the treatment group before being given DSME had a good value of 0% where the value was smaller than the value of motivation after the respondent was given DSME that is equal to 60%. While the motivation of the control group when the initial observation has a good value of 0% and when the final observation has a good value of 10%. The increase in motivation value increased smaller than the assessment of the motivation value of the treatment group,whichwas60%.              DSME application increases patient motivation in preventing recurrence and complications of diabetes mellitus. DSME can be used as a health promotion program to improve self-care capabilities of DM patients.